1972
DOI: 10.1104/pp.50.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethylene on Cell Division and Deoxyribonucleic Acid Synthesis in Pisum sativum

Abstract: Ethylene and supraoptimal levels of 2,4-dichlorophenoxyacetic acid inhibit the growth of the apical hook region of etiolated Pisum sativum (var. Alaska) seedlings by stopping almost all cell divisions. Cells are prevented from entering prophase. The hormones also retard cell division in intact root tips and completely stop the process in lateral buds. The latter inhibition is reversed partially by benzyl adenine. In root tips and the stem plumular and subhook regions, ethylene inhibits DNA synthesis. The magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
68
0
1

Year Published

1974
1974
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 26 publications
6
68
0
1
Order By: Relevance
“…Ethylene has been shown to inhibit cell division, DNA synthesis, and growth in meristems of roots, shoots, and axillary buds of etiolated pea seedlings (1). In the shoot apex, cell division was almost completely annulled by ethylene and only 60% inhibition was observed in the root apex (1).…”
mentioning
confidence: 99%
“…Ethylene has been shown to inhibit cell division, DNA synthesis, and growth in meristems of roots, shoots, and axillary buds of etiolated pea seedlings (1). In the shoot apex, cell division was almost completely annulled by ethylene and only 60% inhibition was observed in the root apex (1).…”
mentioning
confidence: 99%
“…Ethylene or supraoptimal auxin concentration suppresses the growth of pea plants by causing almost complete inhibition of cell division in the apical meristems, lateral buds, and the plumular leaf (2). Furthermore, DNA synthesis in the apical tissue is inhibited by ethylene to the same degree as cell division and at similar hormone concentrations (2).…”
mentioning
confidence: 81%
“…Loss Recent studies on the effects of ethylene on growth of etiolated pea seedlings have shown (2) that the gas suppresses growth of the root and shoot apex, lateral branching, and leaf expansion predominantly by inhibiting cell division. Furthermore, ethylene inhibits DNA synthesis in the plumular hook and subapex region of etiolated pea seedlings (2). Growth inhibition was therefore attributed to inhibition of DNA synthesis by ethylene.…”
mentioning
confidence: 99%
“…In the same study, we demonstrate that endoreduplication is stimulated in a subset of epidermal cells during exposure to ethylene. Early studies demonstrated that ethylene suppresses cell division and mitotic DNA synthesis in apical meristems (Apelbaum and Burg, 1972). However, more recent work on light-grown hypocotyls of Arabidopsis demonstrates that ethylene can both promote hypocotyl enlargement (Smalle et al, 1997) and stimulate endoreduplication (Gendreau et al, 1999), although which cells are affected was not determined.…”
Section: Ethylene Exposure Suppresses Cell Division But Potentiates Cmentioning
confidence: 99%
“…As seedling growth accompanies cell division in the apical meristem, suppression of seedling growth by ethylene implies that the gaseous hormone inhibits both cell elongation and division. Inhibition of DNA synthesis by ethylene was reported in meristems of shoots and roots of pea (Pisum sativum; Burg and Burg, 1968;Apelbaum and Burg, 1972;Eisinger and Burg, 1972) and in wounded tissue of potato (Solanum tuberosum; Sato et al, 1976). Because ethylene's formative effects should include changes in cell division control, we are especially interested in the effects of ethylene on those cells that remain competent for cell division, such as the progenitors of trichomes and stomata.…”
mentioning
confidence: 99%